New Features in FeynArts & Friends, and how they got used in FeynHiggs. (April 2020) - Hahn, T.
Abstract: This note gives an update on recent developments in FeynArts, FormCalc, and LoopTools, and shows how the new features were used in making the latest version of FeynHiggs.